IML495 Welcome to the Museum: Reflecting on Representation & Inclusion in Museum Evaluation. (13th November 2020) - Anderson, Alice; Mileham, Michelle A.
Abstract: "Welcome to the Museum: Reflecting on the Representation and Inclusion in Museum Evaluation" examines how museums have embraced people with different identities (or not) in the last few decades. Drawing on Curator : The Museum Journal 's archives and other museum scholarship, the authors track the impacts of these actions on staffing and professional practice in the profession of museum evaluation. Based on this research, Anderson and Mileham recommend a thorough process of reflection on the level of individuals, departments, and institutions in order to make museum evaluation – and museums writ large – welcoming and supportive of workers and visitors with a variety of identities and perspectives.